Realitas Ekonomi dan Demografi Sebagai Tantangan Peradaban Dunia - Sofi, Siti Lailatus; Muthowif, Muthowif (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2021)
The development of economic realities in Asia and the West, demographics also support the clash of civilizations between Asia and the West, which is a challenge for world civilization. The economic dynamics that are developing in Asia and the West are one of the factors that greatly affect the turmoil of the world economy. This paper examines Asia's economic affirmation of the West, [b] the rise of Islam as Asia's feedback to western ideology, which is the embodiment of acceptance of modernity, and rejection of westernization, and [c] changing the alternative challenges of solvency caused by the Asian economic downturn.